2020
DOI: 10.1002/smll.202004475
|View full text |Cite
|
Sign up to set email alerts
|

Virus Assembly Pathways: Straying Away but Not Too Far

Abstract: viruses, the CPs can self-assemble in vitro around a variety of non-genomic cargo, [6] forming shells that can be structurally identical to those of the wild type (wt) virus. However, wt virus assembly inside the heterogeneous, crowded environment of a host cell cytoplasm surprisingly leads to the large majority of virions being laden with genomic RNA. [7] The reason for non-specific encapsulation in vitro is relatively well understood. [5,8] The main driving force behind assembly at physiological ionic streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 55 publications
10
54
0
Order By: Relevance
“…This suggests that such shells composed only of pentamers are not formed by the full-length BMV CP but only when the 35 N-terminal residues are truncated. 4,26 We also did not observe multiplets (a few protein shells joined together), which confirms that such VLP species are formed only in the presence of a long polyelectrolyte. 4,10,22 Analyzing the topography of both meVLP types, we observed that in each type, one side of the protein shell seems to be better ordered and complete than the opposite side (Fig.…”
Section: Malformed Vlps Group Into Several Non-icosahedral Classes Gi...supporting
confidence: 71%
See 2 more Smart Citations
“…This suggests that such shells composed only of pentamers are not formed by the full-length BMV CP but only when the 35 N-terminal residues are truncated. 4,26 We also did not observe multiplets (a few protein shells joined together), which confirms that such VLP species are formed only in the presence of a long polyelectrolyte. 4,10,22 Analyzing the topography of both meVLP types, we observed that in each type, one side of the protein shell seems to be better ordered and complete than the opposite side (Fig.…”
Section: Malformed Vlps Group Into Several Non-icosahedral Classes Gi...supporting
confidence: 71%
“…However, we detected H12 shells but not H8 shells as Bond et al did. 4 Most probably, H12 is stable enough in the absence of the polyelectrolyte, while the stabilization of the H8 shell requires a polyanion similar to ssDNA that can interact with CP through electrostatic interactions.…”
Section: Malformed Vlps Group Into Several Non-icosahedral Classes Gi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of genomic RNA, retroviruses package cellular RNAs, and retroviral cores can be disrupted upon treatment with RNase [ 35 ]. Moreover, recent work with the non-enveloped brome mosaic virus (BMV) has shown that when capsid subunits assemble on small non-viral RNAs it forms unstable shells with non-icosahedral structures that may be rapidly recycled into icosahedral capsids when the genomic RNA becomes available [ 36 ]. Furthermore, impressive cryo-electron microscopy (cryo-EM) reconstruction of the MS2 bacteriophage demonstrate how distinct, but non-uniformly distributed RNA structures favour assembly of the correct icosahedral capsid structure over non-productive octahedral structures [ 16 ].…”
Section: Packaging Signals In Rna Virusesmentioning
confidence: 99%
“…Furthermore, impressive cryo-electron microscopy (cryo-EM) reconstruction of the MS2 bacteriophage demonstrate how distinct, but non-uniformly distributed RNA structures favour assembly of the correct icosahedral capsid structure over non-productive octahedral structures [ 16 ]. Evidently, optimal viral assembly depends on the biophysical properties of the genomic RNA, which in turn is driven by a myriad of factors, including RNA sequence, structure [ 37 , 38 ] and size [ 36 ].…”
Section: Packaging Signals In Rna Virusesmentioning
confidence: 99%